2023
DOI: 10.3390/brainsci13040579
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of the MIP-1 Family and Their Receptors Reduces Neuropathic Pain Symptoms and Influences Morphine Analgesia: Evidence from a Mouse Model

Abstract: Neuropathic pain pathophysiology is not fully understood, but it was recently shown that MIP-1 family members (CCL3, CCL4, and CCL9) have strong pronociceptive properties. Our goal was to examine how pharmacological modulation of these chemokines and their receptors (CCR1 and CCR5) influence hypersensitivity after nerve injury in Albino Swiss male mice. The spinal changes in the mRNA/protein levels of the abovementioned chemokines and their receptors were measured using RT-qPCR and ELISA/Western blot technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Higher levels of this cytokine are also observed in diabetic neuropathy [19], chemotherapy-induced neuropathic pain [22,95], and a model of partial sciatic nerve ligation [21]. Notably, the neutralization of CCL3 reduces pain-like behavior development in STZ- [19], paclitaxel- [22], CCI- [57], and PSNL-induced [21] neuropathy in mice, which may indicate its significant role in this pathology. Importantly, it is postulated that autoantibodies against CCL3 are biomarkers of type 1 diabetes development [96]; therefore, research on the impact of the modulation of this chemokine on the development of neuropathy should undoubtedly be continued due to its potential therapeutic benefits.…”
Section: Upregulation In Neuropathicmentioning
confidence: 92%
See 4 more Smart Citations
“…Higher levels of this cytokine are also observed in diabetic neuropathy [19], chemotherapy-induced neuropathic pain [22,95], and a model of partial sciatic nerve ligation [21]. Notably, the neutralization of CCL3 reduces pain-like behavior development in STZ- [19], paclitaxel- [22], CCI- [57], and PSNL-induced [21] neuropathy in mice, which may indicate its significant role in this pathology. Importantly, it is postulated that autoantibodies against CCL3 are biomarkers of type 1 diabetes development [96]; therefore, research on the impact of the modulation of this chemokine on the development of neuropathy should undoubtedly be continued due to its potential therapeutic benefits.…”
Section: Upregulation In Neuropathicmentioning
confidence: 92%
“…It was already shown that in a mouse model of diabetic neuropathic pain, strong spinal upregulation of CCL9 is in close association with the development of hypersensitivity [19] and that its neutralization by antibodies reduces pain-related symptoms [19]. Moreover, although in rats [53]/mice [16], increased levels of CCL9 mRNA in the spinal cord and/or DRGs are observed at many time points after injury, the protein level of CCL9 is enhanced between the 1st and 7th days post-CCI [53,57] and 7 days after streptozotocin injection [19]. Therefore, based on published results, we believe that CCL9 plays an important role in the early phase of neuropathic pain development.…”
Section: Upregulation In Neuropathicmentioning
confidence: 98%
See 3 more Smart Citations